General Administration under the New Normal of Private Schools under Jurisdiction of Suphanburi Provincial Education Office - Rukrung, Niphon; Petchroj, Laddawan (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to 1) study the general administration in the new normal, 2) compare the general administration in the new normal of teachers in private educational institutions, classified by gender, educational level and school size and 3) propose guidelines for general administration in the new normal of private education institutions under the jurisdiction of the Suphanburi Provincial Education Office. The samples were 242 teachers of schools under the Suphanburi Provincial Education Office. The research instrument was a questionnaire with a content validity of 0.67-1.00 and a reliability of 0.94. The collected data were analyzed using percentage, mean, standard deviation, independent t-test and one-way ANOVA and LSD. The results of the research were as follows: 1) General administration in the new normal of private educational institutions under the jurisdiction of the Suphanburi Provincial Education Office, both overall and each aspect were at a high level. The aspect with the highest mean was policy and planning for educational institution quality development. It was followed in order by public relations, planning, and building works respectively, and 2) The results of comparing teachers' opinions towards general administration in the new normal of private educational institutions as a whole revealed that gender, education level had no different opinions. But teachers in small and medium sized schools, had different opinions against those in large and extra large sized ones on operational plan of information technology, and building work with a statistically significant difference at the .05. Research suggestions for general administration were schools and classrooms should be regularly sprayed with disinfectants. Also tables, chairs and buildings should always be clean and ready to use. If damaged, it should be maintained so that it can be used as usual.